2007
DOI: 10.1159/000120625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Caffeine on Topographic EEG after Controlling for Withdrawal and Withdrawal Reversal

Abstract: Background/Aims: Despite several decades of research into the effects of caffeine on EEG, few consistent findings have emerged. Notwithstanding the likelihood that differences in methodology may explain some of the inconsistency, confidence in the published findings is undermined by the failure in previous studies to control for the effects of caffeine withdrawal and withdrawal reversal. Methods: Participants (n = 22) alternated weekly between ingesting placebo and caffeine (1.75 mg/kg) 3 times daily for 4 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 92 publications
2
18
3
Order By: Relevance
“…Consistent with these speculations, Keane et al (2007) found that caffeine generally had few and modest effects on EEG power in a study that controlled for withdrawal reversal in ways similar to recent studies of the effects of caffeine on performance, mood and blood pressure (James and Gregg, 2004a,b;. Furthermore, while increases in theta activity were found following caffeine withdrawal (possibly indicating withdrawalinduced sleepiness), similar increases were also observed after acute caffeine challenge following long-term abstinence.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with these speculations, Keane et al (2007) found that caffeine generally had few and modest effects on EEG power in a study that controlled for withdrawal reversal in ways similar to recent studies of the effects of caffeine on performance, mood and blood pressure (James and Gregg, 2004a,b;. Furthermore, while increases in theta activity were found following caffeine withdrawal (possibly indicating withdrawalinduced sleepiness), similar increases were also observed after acute caffeine challenge following long-term abstinence.…”
supporting
confidence: 79%
“…James, 1998;. Whereas we have previously examined acute and chronic effects of caffeine ingestion and caffeine withdrawal (James, 1998;Keane et al, 2007), the present study focused on chronic effects while introducing the additional variable of sleep restriction. In brief, with participants serving as their own controls over the successive weeks of the experiment, effects were examined while participants were normally rested and when sleep restricted, with and without caffeine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that a direct effect on muscle fiber or lower motor neuron is relevant [5,9]. On the other hand, the central effect is large and well documented [19,[27][28][29][30][31][32][33][34]. CSP as estimated using low intensities is a sensitive method to detect the influence of caffeine on the central nervous system [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the EEG changes are not striking and are possibly influenced by acute caffeine withdrawal or ingestion [33,34].…”
Section: Cognitive Functionmentioning
confidence: 96%